Piezoelectric and mechanical properties of CaO reinforced porous PZT ceramics with one-dimensional pore channels. Issue 2 (1st February 2017) - Liu, Wei; Liu, Wenting; Wang, Yanzhong; Xue, Chaorui; Wang, Jianhong; Yang, Jinlong
Abstract: The formation of capillaries in sodium alginate gels is a dissipative process driven by unidirectional diffusion of divalent cations into sodium alginate sols. In the present work, we have prepared 3-1 type porous lead zirconate titanate (PZT) ceramics with oxides (CaO) being doped on a molecular level from the dissipative process by incorporating PZT particles into the sodium alginate gel matrix. By varying the concentration of cation solutions (CaCl2 ) from 0.5 mol/L to 2.5 mol/L, both the microstructure, doping amount of oxides (CaO) and crystalline phase of the porous PZT ceramics were tailored. Accordingly, increase in the concentration of Ca 2+ has led to a reduction in the relative permittivity ( ε r ) first, and then an increase, while the piezoelectric coefficient ( d 33 and d 31 ) demonstrated an opposite variation tendency. The prepared samples possessed a maximal HFOM value of 4755×10 –15  Pa −1 when the concentration of Ca 2+ was 1.0 mol/L. Addition of CaO was found to improve the compressive strength of porous PZT ceramics, which was preferential to promoting the stability and reliability for application.